Management of Mevalonate Kinase Deficiency: A Pediatric Perspective - Jeyaratnam, Jerold; Frenkel, Joost (Frontiers in Immunology, 2020)
Background: Mevalonate kinase deficiency (MKD) is an inborn error of metabolism leading to a syndrome characterized by recurrent inflammation. This clinically manifests itself as fever and can be accompanied by gastrointestinal symptoms, oral ulcers, cervical lymphadenopathy and skin rash. Methods: We searched Pubmed, Embase, Cochrane and CINAHL for relevant articles. All articles were screened by both authors. Relevant articles were included in this review. Results: The interleukin-1 antagonist canakinumab is the only well-studied and effective treatment for MKD patients with 35% of patients reaching complete remission in a large randomized controlled trial. Other therapeutic options include glucocorticoids and the IL-1 antagonist anakinra, although the level of evidence for these treatments is weaker. If patients fail to these treatments, the biologicals etanercept or tocilizumab can be used. Mildly affected patients might benefit from cheaper, less invasive treatments such as paracetamol and NSAIDs. Conclusion: Canakinumab is the only evidence-based treatment for mevalonate kinase deficiency. However, the costs limit availability for many patients. Cheaper and more readily available options include glucocorticoids, anakinra, etanercept and tocilizumab, although there is limited evidence supporting these treatments.